Psicoprofilaxis obstétrica: características y beneficios en las gestantes atendidas en el Centro de Salud Las Piñas- Milagro, noviembre 2023- abril 2024. - Jiménez Peralta, Ginger Katiuska (2024)
Obstetric Psychoprophylaxis is a comprehensive preparation that is offered during pregnancy, childbirth and/or postpartum. The objective of this research project is to determine the characteristics and benefits of Obstetric Psychoprophylaxis in patients treated at the Las Piñas health center – Milagro, November 2023 – April 2024. The methodology applied was descriptive, non-experimental, cross-sectional cohort using a qualitative and quantitative approach. The information was collected through a survey directed at a specific group of patients who participated in the Obstetric Psychoprophylaxis Program at the Las Piñas-Milagro Health Center. The sample consisted of 88 patients according to the inclusion and exclusion criteria. The results of this research study revealed a sociodemographic diversity, the average age was 20 to 30 years with 68%, the level of secondary education completed or in progress with 73% and the majority only had one child with the 46. %. Compliance with attendance at the 6 sessions of Obstetric Psychoprophylaxis was highlighted as a relevant characteristic with 69%. Maternal benefits were observed, such as reduced anxiety during pregnancy and childbirth by 85% and 82% respectively, and neonatal benefits, with a lower need for medical interventions of the newborn after delivery, with 89%. In addition, it was found that 85% of the patients who participated in Obstetric Psychoprophylaxis showed a greater tendency to vaginal delivery.